ANALISIS KEBUTUHAN PENDIDIKAN AGAMA KRISTEN DALAM MENUMBUHKAN MORAL KRISTIANI ANAK USIA DINI - Monang Sianturi (Institut Agama Kristen Negeri Tarutung, 2020)
This study aims to analyze the needs of Christian religious education in fostering early Christian morals. This research was concuded at the early childhood education programs Intitut of Sipoholon sub- District North Tapanuli regency in 2018. The object of research is the teachers of Sipoholon. Earned value overall analycis of the needs for Christian religious education in fostering the children of early childhood education programs in Sipoholon sub- district, North Tapanuli regency in 2018 is 3,07 and this value is in the good category. The result of the data calculation are on a scale 2,60-3,59. That means that teacher have tried to poster chidrens morality through Christian religious education. But in some teaching the teaher has not maximally known the importance Christian education in fostering Christian morality in early childhood.BAHASA INDONESIA ABSTRACT: Penelitian ini bertujuan untuk menganalisis kebutuhan Pendidikan Agama Kristen dalam Menumbuhkan Moral Kristiani Anak Usia Dini. Penelitian ini dilaksanakan di Lembaga PAUD Se-Kecamatan Sipoholon Kabupaten Tapanuli Utara Tahun 2018, yang menjadi objek penelitian ini adalah guru-guru PAUD se-Kecamatan Sipoholon Kabupaten Tapanuli Utara. Diperoleh nilai keseluruhan Analisis Kebutuhan Pendidikan Agama Kristen dalam Menumbuhkan Moral Kristiani Anak PAUD Se- Kecamatan Sipoholon Kabupaten Tapanuli Utara Tahun 2018 adalah 3,07 dan nilai ini berada pada kategori baik, hasil perhitungan data berada pada skala 2,60-3,59 berarti hipotesa diterima. Hal tersebut memperlihatkan bahwa guru sudah berupaya menumbuhkan moralitas anak melalui pendidikan Agama Kristen. Namun pada sebahagian pengajaran guru belum maksimal mengetahui pentingnya Pendidikan Agama Kristen dalam menumbuhkan moralitas kristiani anak usia dini.Keywords: Christian religious education, Christian moral of kids.